Histological diagnosis of Bechterew’s disease on exhumed female remains in Bosnia and Herzegovina: a case report - Dervisevic, Emina; Dorić, Mirsad; Salihbegović, Adis; Čamdžić, Nina (International Journal of Research in Medical Sciences, 2023)
Ankylosing spondylitis is a serious ailment that affects people, and the first signs or symptoms usually occurr between the ages of 15 and 45. While the condition is mostly prevalent in men, women are not immune to this disease. This problem is diagnosed with a combination of clinical history and X-rays, pathology and HLAB27 test. The aim of this case study is to demonstrate how macroscopic and microscopic analysis can be used for identification of the disease from a forensic point of view. In April 2018, we exhumed 11 remains near the city Višegrad, twenty-five years after the last war. All the remains were completely skeletonized. The skeleton of a female was specific and shaped like a bamboo branch, with a partial knitting of vertebral bodies in the lumbar region of spine and with total knitting in the thoracic part. The spinous processes were completely knitted. Her son gave informations for verbal autopsy that she had trouble walking and doing normal activities during life. Samples for analysis and pathological diagnostics were used to determine the real bone condition for forensic purposes. To our best knowledge our case is first one in the literature which combines macroscopic and microscopic analysis of AK in exhumed skeletal remains after 25 years of death in modern era of Europe.